Der frühchristliche Märtyrer und der stoische Weise Eine topologische Untersuchung - Trelenberg, Jörg 1965- (2011)
Early Christian martyrology presents its protagonists almost uniformly as heroic figures: They hold on to their beliefs, they neglect physical pain and they are not afraid of death. Thus a Christian martyr stays calm and tempered even if subjected to severe distress and masters every situation with dignity. Another idealized character is the stoic sage. Similarly, he keeps his “stoic” countenance: he will not accept alterations of his emotional status and instead welcomes whichever fate he meets, since in his view following and accomplishing one's divine destiny outranks saving one's own life. The attribution of similar qualities and character traits to the vir sapiens of stoic philosophy on the one hand and to the martyr of the Christian church on the other, as seen in many literary representations, inevitably raises the question of (literary) interdependence. The answer to this question has to be multifaceted: Early Christian martyrology includes examples of direct influence of Stoicism (a), of indirect adoption of motifs taken over from Stoicism via Jewish martyr literature (b) or via philosophical syncretism in the Roman Principate (c); in addition to these, one has to assume the possibility of independent creation (d).